Primary malignant mucosal melanoma of the maxillofacial area - Kim, Hyounmin (J Korean Assoc Oral Maxillofac Surg, 2021)
OBJECTIVES: We aimed to collect and report data from all patients who have been diagnosed with mucosal malignant melanoma to obtain the epidemiology and principles of current treatments. MATERIALS AND METHODS: Between January 2008 and December 2018, 20 patients underwent surgery or follow-up observations at Yonsei University Dental Hospital. The patients’ clinical information was reviewed retrospectively. RESULTS: Seventeen of 20 patients had undergone definitive surgery, while only 6 patients received adjuvant radiotherapy or systemic therapy. Eight of 20 patients, including those that had recurrent lesions, were provided immunotherapy. The 3-year survival for all stages was 50%, with a local recurrence rate of 75% and a metastasis rate of 65%. CONCLUSION: The overall survival of patients receiving surgical treatment was longer than that of patients who did not undergo surgical resection. Eight of 20 patients received immunotherapy as the first-line regimen at our clinic, and those patients exhibited longer overall survival compared to patients in reported keynote studies.